A PHILOSOPHICAL VIEW OF NEW UZBEKISTAN REALITY - Shokirov Rustam Uroqovich (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The renewal processes taking place in Uzbekistan are fundamentally different in character from the previous ones. This is the result of changes in the economic, political and spiritual spheres. In the period of renewal, cases of acceleration in all spheres of society’s life were considered. It is not possible for each of these renewed areas to develop independently, acquire a new content and form. As a result of their interaction with each other, a system of development of the entire society is formed. It is important to consider the nature and character of this process in the knowledge of social phenomena. Therefore, every member of the society needs to approach it from a philosophical and scientific point of view in order to know the phenomena that surround him, in which he directly participates. Taking this into account, in this article we set ourselves the goal of analysing about the uniqueness of the philosophical approach to the life of society and the processes that take place in it.